Pengembangan Pembelajaran Seni Tari Berbasis Teknologi Digital bagi Peserta Didik di Era Pendidikan Digital: Analisis Studi Literatur - Hasanah, Uswatun; Fuji Astuti; Nerosti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has driven changes in dance learning practices, particularly in the use of media and learning strategies that are more adaptive to student characteristics. However, various studies related to digital technology-based dance learning still tend to be fragmented and focus on the use of specific media separately, thus not providing a complete picture of the pedagogical function of technology in dance learning. This article aims to analyze and map various forms of digital technology and their pedagogical functions in the development of dance learning, particularly in the context of elementary education. This research uses the Systematic Literature Review (SLR) method by examining scientific articles relevant to the topic of digital technology-based dance learning. The results of the study indicate that visual digital media plays a role in supporting the understanding of movement structure and details, online learning platforms facilitate learning management and reflection, interactive applications increase engagement and personalization of practice, and social media opens up space for creative expression and collaborative appreciation. The integration of various forms of digital technology shows that dance learning becomes more effective when technology is designed in an integrated manner and aligned with the learning objectives and characteristics of movement-based learning. These findings provide conceptual implications for the development of dance arts learning designs that are more systemic, adaptive to technological developments, and still uphold the values ​​of creativity and aesthetic experiences of students.